Three-week video- and home-based training program for people with ataxia: a pilot randomized controlled trial - Rentz, Clara; Reinhardt, Alisha; Jung, Naomi; Vanchinathan, Vignesh; Peterburs, Jutta; Jacobi, Heike; Timmann, Dagmar; Thieme, Andreas; Brötz, Doris; Bellebaum, Christian; Schnitzler, Alfons; Amunts, Katrin; et al. (Movement disorders clinical practice, 2025)
Background Gait and balance impairment is a disabling clinical feature in people with degenerative cerebellar ataxia. Objectives We performed a rater-blinded, parallel 3-arm randomized controlled trial with delayed-start-design (exploratory proof-of-concept study) to assess whether, compared to control, people with mild/moderate hereditary ataxia benefit from additional video-based training with different frequencies, and how clinical characteristics interact with training success. Methods Digital gait/balance measures were assessed before and after a three-week video-based training program at home (Train20: 4 × 20min/week, n = 11; Train40: 2 × 40min/week, n = 11; control: standard medical care, n = 10). Group differences at baseline and changes over time were assessed using ANOVA. Linear mixed models were conducted to examine the influence of clinical variables on outcomes over time. Further exploratory analyses were performed using intraclass correlation coefficients (ICC), and paired t-tests within each group. Results All variables showed good to excellent test-retest reliability (ICC ≥0.69). No significant interactions between group and measurement time were found for clinical or gait/balance variables (p ≥ 0.338). However, participants with higher initial disease severity, greater impairment in activities of daily living, and better well-being showed significant improvements in feet-together stance (p = 0.04), normal (p = 0.01), and backward gait (p = 0.03). Exploratory analyses showed improvement only in Train40. Conclusions Although the protocol did not lead to general improvements in people with mild/moderate ataxia, irrespective of training frequency, those with higher initial disease severity, higher functional impairment, and better mental well-being showed significant benefits. Greater attention should be given to the impact of well-being to enhance motor training outcomes. Longer, less frequent sessions may offer greater potential for improvement.